PERBANDINGAN KADAR TIROKSIN (T4) DALAM SERUM SAPI PERANAKAN ONGOLE YANG BERFOLIKEL OVARIUM KECIL DAN BESAR - , ARUM PAMINTANING HERMALIS, Dr. drh. Rr. Amelia Hana, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The hormones thyroxine (T4) is the result of a synthesis of the thyroid gland, it has an important role in helping maintain homeostatis and reproduction system. The existence of the T4 hormone levels can indicate the status of the reproduction, like the function of the ovary and development of follicles. Research was conducted to find out the comparison of the levels of thyroxine (T4) between small ovarian follicular and large ovarian follicular in cow serum. In the research used 10 cows which 5 cows have small follicle and the other have large follicle of ovarian. Blood samples taken from the jugular vein about 5 ml, and then examined using a ELISA commercial kit. The results of the study showed that the bovine serum which has a small follicles (<5 mm) is on the average level of 22,35 ng/dl+ 7,21, while in bovine serum which has a large follicles (>5 mm) averaged 19,90 ng/dl+ 1,70. Results of statistical analysis showed that no significant difference (P> 0,05) between average levels of T4 hormone in the bovine serum of cows who have small and large follicles of ovarian, so it can be concluded that the action of the hormone T4 in the cattle with small and large follicle is unlike.